2021
DOI: 10.1093/rpd/ncab025
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodule Detection in Chest Ct Using a Deep Learning-Based Reconstruction Algorithm

Abstract: This study’s aim was to assess whether deep learning image reconstruction (DLIR) techniques are non-inferior to ASIR-V for the clinical task of pulmonary nodule detection in chest computed tomography. Up to 6 (range 3–6, mean 4.2) artificial lung nodules (diameter: 3, 5, 8 mm; density: −800, −630, +100 HU) were inserted at different locations in the Kyoto Kagaku Lungman phantom. In total, 16 configurations (10 abnormal, 6 normal) were scanned at 7.6, 3, 1.6 and 0.38 mGy CTDIvol (respectively 0, 60, 80 and 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Channelized Hotelling Observer (CHO) model observer correlate well to human performances, especially for simple tasks such as a detection of a signal in a small region of interest for different anatomical area. Many studies have shown that model observer can correlate well with human performance include the detection of discs in white noise and clustered lumpy backgrounds [20], microcalcification in mammography [21], breast tomosynthesis [22] nodules in computed tomography (CT) ramp-noise spectrum [23], nodules in breast cone beam CT [24], lung region [25,11] and an abdominal CT acquisition [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Channelized Hotelling Observer (CHO) model observer correlate well to human performances, especially for simple tasks such as a detection of a signal in a small region of interest for different anatomical area. Many studies have shown that model observer can correlate well with human performance include the detection of discs in white noise and clustered lumpy backgrounds [20], microcalcification in mammography [21], breast tomosynthesis [22] nodules in computed tomography (CT) ramp-noise spectrum [23], nodules in breast cone beam CT [24], lung region [25,11] and an abdominal CT acquisition [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…How to accurately locate and detect lung nodules so as to detect, diagnose, and treat lung nodules as early as possible is worthy of our attention [ 7 , 8 ]. Lung nodule detection algorithms generally mainly consist of image analysis and pattern recognition.…”
Section: Introductionmentioning
confidence: 99%
“…The SCPM-Net was tested on the LUNA16 dataset and achieved an average sensitivity of 89.2% at 7 FPs per image for lung nodule detection. Franck et al [ 121 ] investigated the effects on the performance of deep learning image reconstruction (DLIR) techniques on lung nodule detection in chest CT images. In this study, up to 6 artificial nodules were located within the lung phantom.…”
Section: Lung Cancer Prediction Using Deep Learningmentioning
confidence: 99%